Processing, Microstructure And Properties Of In Situ Copper Reinforced Tungsten Carbide Nanostructured Composite - Yusoff, Mahani (2012)

(untitled)
The present work investigates characteristics and properties of in situ nanostructured copper-tungsten carbide composite prepared by mechanical alloying (MA) and powder metallurgy (PM). Elemental powders of Cu (copper), W (tungsten) and graphite (C) were milled in a planetary ball mill using different ball size, milling time and milling speed. Then the product was compacted at different pressures and sintered at different temperatures and times. In situ tungsten carbide phases (WC and W2C) were only present after a combination of MA and sintering. W2C was first to be observed and the formation of WC began with longer milling times and speeds, in accordance to a decreased crystallite size and an increased of internal strain of Cu during MA. W2C was formed as a result of C deficiency whereas WC through transformation from W2C to WC during sintering.